Disentangling the origins of branched tetraether lipids and crenarchaeol in the lower Amazon River: Implications for GDGT‐based proxies. (15th January 2013) - Zell, Claudia; Kim, Jung-Hyun; Moreira-Turcq, Patricia; Abril, Gwenaël; Hopmans, Ellen C.; Bonnet, Marie-Paule; Sobrinho, Rodrigo Lima; Damsté, Jaap S. Sinninghe
Abstract : To trace the origin of branched glycerol dialkyl glycerol tetraethers (brGDGTs), their distribution in soils and suspended particulate matter (SPM) of Amazonian rivers and floodplain lakes ( várzeas ) was studied. Differences in distribution between river SPM and surrounding (lowland) soils suggests an additional brGDGT source to eroded soils in the lowland drainage basin. Erosion of high Andean soils (above 2500 m in altitude) has no major influence because its brGDGT distribution differs substantially from that in river SPM. Furthermore, SPM in the Tapajós River, a tributary that does not derive from the Andes, has a virtually identical brGDGT distribution to that of the Amazon main stem. The higher proportion of phospholipid‐derived brGDGTs in river SPM compared to soils indicates that in situ production in the Amazon is an additional source for riverine brGDGTs. This affects the methylation and cyclization index of brGDGTs (MBT‐CBT), resulting in slightly lower MBT‐CBT‐derived temperatures and slightly higher CBT‐derived pH values, i.e., between the pH of the basin soil and that of the river. Since the difference between MBT‐CBT‐derived temperatures of Amazon River SPM and the surrounding soils is relatively small (2°C) compared to other aquatic systems (for lakes a difference of ∼ 10°C has been observed), it might still be possible to trace large climate changes in the Amazon basin with the MBT‐CBT using river fan cores. However, variations in in situ production of brGDGTs in the Amazon River over time and space have to be evaluated in the future. Likewise, in situ production may affect the application of the MBT‐CBT paleothermometer in other river systems. Our results also show that crenarchaeol is primarily produced in the Amazon River and that its varying production influences the branched vs. isoprenoid tetraether (BIT) index. This indicates that the BIT index not only represents the input of soil organic carbon to the river but is also affected by in situ production of brGDGTs and crenarchaeol.